Community Assembly Theory as a Framework for Biological Invasions - Pearson, Dean (2018)
Biological invasions present a global problem underlain by an ecological paradox that thwarts explanation: how do some exotic species, evolutionarily naïve to their new environments, outperform locally adapted natives? We propose that community assembly theory provides a framework for addressing this question. Local community assembly rules can be defined by evaluating how native species’ traits interact with community filters to affect species abundance. Evaluation of exotic species against this benchmark indicates that exotics that follow assembly rules behave like natives, while those exhibiting novel interactions with community filters can greatly underperform or outperform natives. Additionally, advantages gained by exotics over natives following disturbance can be explained by accounting for extrinsic assembly processes that bias exotic traits toward ruderal strategies.